(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Abundant movements on environmental and carbon emission issues have been going on formore than decades while researchers have lot of innovation to decrease carbon emission byimproving the internal combustion engine of an automobile, however, none of this prove tolesseningcarbonemissionduetomajorfactthatthenumberofvehiclesareincreasingondailybasis. Consequently, this work delivers an inclusive review, design, and development of a Thermo-ElectricGenerator(TEG)systemthatwillproducepowerfromtheunusedheatenergygenerated by an internal combustion engine through the exhaust gas conduit. This explorationworkprovidesanenhancedstructuraldesignofthesystembyintroducingcoolingfinsaccompanied on the cold side of the TEG, in order to maintain the temperature at a constantlevel. According to the output power generated from the proposed TEG system, it is observedthat when the temperature difference between the hot side and cold side of the TEG ismaximum,theoutputpowerelectricitygeneratedfromthesystemreachesthemaximum.Thusresultinginusefullowpowergenerationfromthefuelenergywastedinexhaustedgasesbytheinternalcombustion engines.